Compliance with surgical antibiotic prophylaxis for obstetric and gynecologic surgeries in Nigeria: a retrospective study - Abubakar, Usman (Elsevier Ltd, 2019)
Surveillance of surgical antibiotic prophylaxis provides useful information that could be used to identify key areas to implement antimicrobial stewardship interventions. There is limited evidence to describe the compliance with surgical antibiotic prophylaxis in obstetric and gynecologic settings in Nigeria. The objective of this study was to evaluate the compliance with timing and duration of surgical antibiotic prophylaxis among patients who had obstetric and gynecologic procedures.